REGISTERS IN CARDIOLOGY: THEIR PRINCIPLES, RULES, AND REAL-WORD POTENTIAL - S. A. Boytsov; S. Yu. Martsevich; N. P. Kutishenko; L. Yu. Drozdova; M. M. Lukyanov; A. V. Zagrebelnyi; M. I. Ginzburg (Кардиоваскулярная терапия и профилактика, 2013)
The article presents the main goals, tasks, principles, and methodological aspects of the cardiology register development. The authors describe the main types of registers, provide the examples, and specify the key principles of the register development and maintenance. In addition, they discuss the role of both long- and short-term registers in solving a wide range of important research tasks, particularly in the areas of effectiveness and safety of cardiovascular pharmacotherapy and the survival prognosis for specific nosological forms. The task-specific limitations of registers are also discussed.